Towards modern municipal sports and recreation management in Costa Rica - Mosquera Vargas, Allan (2007)
Sports and recreation management is addressed here using a model that combines the policies and methodologies applied in the Costa Rican context as a result of a concern to identify the real needs in the sports, recreation, and health promotion fields through the different manifestations of human movement.  This approach has been developed during eight years of work in the Costa Rican Sports and Recreation Institute (Instituto Costarricense del Deporte y la Recreación-ICODER) together with different Costa Rican communities, both rural and urban, and local organizations, such as Comprehensive Development Community Associations, Sports and Recreation Community Boards (CCDR), Municipal Mayorships, and NGOs, among others.  This article particularly takes into consideration the experience of the CCDRs as entities that have been given the responsibility by the Costa Rican Government to promote and manage municipal sports and recreation services with a convenient offering that would meet the needs of users or customers.  In this way, this article is aimed at answering the question on how Boards should conduct an efficient management in a way that they also meet the needs of public users or customers in the municipalities of the country, by proposing a management model that serves as an additional instrument to improving the already existing services managed by the aforementioned entities.  This study presents a model of Costa Rican management structured with the theoretical elements that currently define the organization and planning of sports and recreation as a service.